Murder thy neighbor : [large type] true-crime thrillers - Patterson, James, 1947-; Bourelle, Andrew; DiLallo, Max (Patterson, James, 1947-. Murder is forever series, 2020)
As seen on Discovery ID, these two true-crime thrillers follow a neighbors' quarrel that turns violent and cyber-bullying that explodes in a double murder.Murder Thy Neighbor: Ann Hoover is a nice woman but she's come to hate her neighbor. Roy Kirk moved in next door with plans to renovate. But as the weeks go by, his DIY construction turns to shambles. When Ann takes him to court, Kirk's retaliation will be shockingly gruesome.Murder IRL: Jenelle Potter has always been better at connecting with people through social media. With overprotective parents, she hasn't had very many options to meet people, until she links up with Billy. But her feelings for Billy are unreciprocated, causing Jenelle to start a virtual war--a war enters the real world.